2018
DOI: 10.1002/ejlt.201700306
|View full text |Cite
|
Sign up to set email alerts
|

Binary Mixtures of Tripalmitoylglycerol (PPP) and 1,3‐Dipalmitoyl‐2‐stearoyl‐sn‐glycerol (PSP): Polymorphism and Kinetic Phase Behavior

Abstract: The kinetic phase behavior and phase transformation paths of tripalmitoylglycerol (PPP) and 1,3‐dipalmitoyl‐2‐stearoyl‐sn‐glycerol (PSP) mixtures are investigated at 10.0 °C min−1 (fast cooling) and 1.0 °C min−1 (slow cooling) cooling rates, and re‐heating at 5.0 and 1.0 °C min−1. Mixtures with 0.1 XPSP increments are studied in terms of polymorphism, crystallization, and melting. At the higher cooling rate, all samples crystallized in the α polymorph, while at the lower cooling rate, samples containing XPSP ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
(54 reference statements)
3
19
0
Order By: Relevance
“…At the higher cooling rate, it was already concluded that PSP drives the overall crystallization process. In our previous study, [14] mixtures of PPP-PSP, when cooled at 1.0 C min À1 , crystallized in the β 0 -form when X PSP ! 0.2.…”
Section: Pure Componentsmentioning
confidence: 88%
See 4 more Smart Citations
“…At the higher cooling rate, it was already concluded that PSP drives the overall crystallization process. In our previous study, [14] mixtures of PPP-PSP, when cooled at 1.0 C min À1 , crystallized in the β 0 -form when X PSP ! 0.2.…”
Section: Pure Componentsmentioning
confidence: 88%
“…0.5, which could be associated with the presence of the more stable β 0 1 -form. [14] In the PSS-PSP mixtures, however, the peak temperatures slightly decreased when PSP concentration was increased (X PSP 0.5, dotted line in Figure 2b), followed by a linear increase in the peak temperature at higher PSP concentrations (X PSP ! 0.6).…”
Section: Pure Componentsmentioning
confidence: 95%
See 3 more Smart Citations